MBD5 and MBD6 interact with the human PR‐DUB complex through their methyl‐CpG‐binding domain. Issue 19 (24th April 2014) - Baymaz, H. Irem; Fournier, Alexandra; Laget, Sophie; Ji, Zongling; Jansen, Pascal W. T. C.; Smits, Arne H.; Ferry, Laure; Mensinga, Anneloes; Poser, Ina; Sharrocks, Andrew; Defossez, Pierre‐Antoine; Vermeulen, Michiel; et al.
<x xml:space="preserve">Abstract</x> MBD5 and MBD6 are two members of the methyl‐CpG‐binding domain (MBD) family of proteins that are poorly characterized. Studies performed thus far have failed to show binding of the MBD5 and MBD6 MBD to methylated DNA. Here, we show that both MBD5 and MBD6 interact with the mammalian PR‐DUB Polycomb protein complex in a mutually exclusive manner. Strikingly, the MBD of MBD5 and MBD6 is both necessary and sufficient to mediate this interaction. Chromatin immunoprecipitation analyses reveal that MBD6 and FOXK2/PR‐DUB share a subset of genomic target genes, suggesting a functional interaction in vivo. Finally, we show that MBD6, but not MBD5, is recruited to sites of DNA damage in a PR‐DUB independent manner. Our study thus implies a shared function for MBD5 and MBD6 through an interaction with PR‐DUB, as well as an MBD6‐specific recruitment to sites of DNA damage.